2022
DOI: 10.3390/jpm12060870
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Based Difference in the Effect of Metoprolol on Heart Rate and Bradycardia in a Population-Based Setting

Abstract: Background: Metoprolol, a beta-blocker, is used to reduce the heart rate. Although it has been demonstrated that the metoprolol plasma concentration is higher in women than in men, the same dose is recommended. In this study, we investigated whether the metoprolol concentration was associated with a stronger heart-rate reduction and bradycardia in women than in men. Methods: This study is part of the Rotterdam Study (RS), a population-based prospective cohort study. Blood samples from a random subset of 2000 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although this has to be confirmed in future prospective research, the higher dose-and age-adjusted drug/metabolite concentrations we observed in females are likely to contribute to the higher risk of ADRs described for multiple drug classes, including beta-blockers metabolized by CYP2D6. 32,33 Data regarding the risk of ADRs in females treated with allopurinol are more scarce, but lean toward an increased risk in older females. 34 Interestingly, in our study, more than half of females also reported previous drug allergies and intolerances to medication, which was consistently more than what was reported in males.…”
Section: Discussionmentioning
confidence: 99%
“…Although this has to be confirmed in future prospective research, the higher dose-and age-adjusted drug/metabolite concentrations we observed in females are likely to contribute to the higher risk of ADRs described for multiple drug classes, including beta-blockers metabolized by CYP2D6. 32,33 Data regarding the risk of ADRs in females treated with allopurinol are more scarce, but lean toward an increased risk in older females. 34 Interestingly, in our study, more than half of females also reported previous drug allergies and intolerances to medication, which was consistently more than what was reported in males.…”
Section: Discussionmentioning
confidence: 99%
“…60 This means that dose adjustments should not be neglected to avoid adverse events (AEs). 61 Women also have a higher incidence of druginduced liver toxicity, gastrointestinal AEs due to NSAIDs, allergic skin rashes (up to 2-fold), cough with ACE-I (2-fold), hemorrhagic complications with anticoagulants, platelet antiaggregants and thrombolytics, and myopathy with statins. 21 Studies found that 74% of cases of acute liver failure due to drug toxicity appear in women, over 50% of them occurring using therapeutic doses of medication.…”
Section: Adverse Drug Reactionsmentioning
confidence: 99%
“… 79 Thus, a greater reduction in heart rate and blood pressure and a significantly increased risk of bradycardia have been reported in women. 80 …”
Section: Pharmacodynamic and Pharmacokinetic Differences In The Elderlymentioning
confidence: 99%